2013
DOI: 10.1074/jbc.m113.511410
|View full text |Cite
|
Sign up to set email alerts
|

Factor V Activator from Daboia russelli russelli Venom Destabilizes β-Amyloid Aggregate, the Hallmark of Alzheimer Disease

Abstract: Background: ␤-Amyloid aggregate formation and its destabilization are addressed in Alzheimer disease. Results: Peptides synthesized using Russell's viper venom factor V activator as a template can destabilize ␤-amyloid fibril and inhibit cytotoxicity. Conclusion: These peptides dissociate ␤-amyloid fibrils to the nontoxic monomeric state. Significance: This study explores possibility of designed peptides for clinical applications in Alzheimer disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 39 publications
(37 reference statements)
0
17
1
Order By: Relevance
“…This was deduced from the fact that residues 162–167 of thrombin corresponded to 141–147 of RVV‐V (Fig. A); the latter showed homology to the sticky region ‘QKLVFFAE’ of Aβ42 . This information coupled to the previous initial observation that proteolytically digested thrombin could destabilize Aβ fibrillar aggregates (Fig.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…This was deduced from the fact that residues 162–167 of thrombin corresponded to 141–147 of RVV‐V (Fig. A); the latter showed homology to the sticky region ‘QKLVFFAE’ of Aβ42 . This information coupled to the previous initial observation that proteolytically digested thrombin could destabilize Aβ fibrillar aggregates (Fig.…”
Section: Resultsmentioning
confidence: 61%
“…It has previously been reported that small peptides derived from Russell’s viper venom (RVV)‐V potentially destabilized Aβ aggregate . Although RVV‐V and thrombin exhibit functional similarity, sequence wise they have limited homology.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another previous study revealed that FA5 polymorphisms confer an increased risk of ischemic stroke in younger adults (24). Furthermore, Bhattacharjee et al reported that the FA5 activator might be associated with Alzheimer's disease; the FA5 activator destabilized Aβ aggregates, which may be useful for disease prevention in the future (25). An earlier study found that the risk of dementia increased 2.11-fold in carriers of the FA5 Leiden mutation relative to subjects lacking this mutation [95% confidence interval [CI] 0.93-4.77].…”
Section: Discussionmentioning
confidence: 98%